Audit Keamanan untuk Mendeteksi Kerentanan dan Mitigasi pada Website UPT Integrated Laboratory (ILab) ITERA Berbasis OWASP Zed Attack Proxy (ZAP) - Ilham Firman Ashari Ashari; Muhammad Affandi; Hendri Tri Putra; Muhammad Telaga Nur (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Information technology now has many positive and negative effects on comfort. One of the negative effects of this technology is high level security attacks that can exploit various vulnerabilities and loopholes. Vulnerability testing (security audits) is therefore necessary to identify and overcome the vulnerabilities of the risks raised. The author is UPT Terpada Laboratory (Ilab) ITERA (https:http://ilab.itera.ac.id), a website maintained by his UPT Institute at the University of Technology Sumatra. This website contains all information about the labs of the University of Technology of Sumatra. Security audits are performed using the OWASP ZAP tool. A security check was performed on web ilab.itera.ac.id and the high priority alert results are: 1 vulnerability, medium priority warning: Three vulnerabilities, low priority warnings: Seven vulnerabilities and information: 3 vulnerabilities.